MASA KERJA DAN USIA BERHUBUNGAN DENGAN PRAKTIK KOLABORASI INTERPROFESIONAL PADA RAWAT INAP RUMAH SAKIT - Sulistyaningsih; Nuli Nuryati Zulala; Fitnaningsih Endang Cahyani; Sri Lestari (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: The practice of interprofessional collaboration is one of the elements that determines the quality of inpatient services. As a result of dysfunctional or non-existent interprofessional collaborative health practices is a medical error, which is the leading cause of death worldwide. Objective: to analyze factors related to interprofessional health collaboration in hospital hospitalization. Methods: Survey research methods, with cross sectional approach. The sample of this study were doctors and health workers who provided care for 58 inpatients at PKU Muhammadiyah Gamping Hospital in June-July 2019 determined by consecutive sampling. Data was collected by filling out the Collaborative Practice Assessment Tool (CPAT) questionnaire. Data analysis with chi-square. Results: the practice of interprofessional collaboration in hospitalization is mostly good (mean index = 3.00). Years of service and age are significantly related to the practice of interprofessional collaboration in hospital hospitalization. Type of profession, gender, education, marital status and income are not related to the practice of interprofessional collaboration in hospital hospitalization. Conclusion: The higher the work period and age of the healthcare professional, the better the practice of interprofessional collaboration in hospital hospitalization.